Pengaruh Kompetensi dan Budaya Kerja terhadap Person Job Fit dan Kinerja Karyawan pada PT. Andromedia - Lutfiyah, Lutfiyah; Oetomo, Hening Widi; Suhermin, Suhermin (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
PT Andromedia is a private company engaged in IT Development located at Jalan Gayung Kebonsari Perum Graha Indah F21-22 Surabaya. This study aims to analyze the influence of competence and work culture on person-job fit and employee performance at PT Andromedia. The population in this study amounted to 68 employees and the sampling technique used was saturated sampling meaning that the entire population would be sampled. The tool for analyzing data in this study uses the Partial Least Square (PLS) analysis method that is run with SmartPLS 3.0 software. The test results have 5 hypotheses, among others, first, competence has no significant effect on a person-job fit. Second, work culture has a significant influence on a person-job fit. Third, competence has a non-significant effect on employee performance. Fourth, work culture has a significant effect on employee performance. Fifth, the person-job fit has a significant influence on employee performance.